A new compact structure for a high intensity low-energy heavy-ion accelerator - 王志军 何源 A. A. Kolomiets 刘淑会 杜晓楠 贾欢 李超 王旺生 陈熙萌 (Chinese physics C, 2013)
A new compact accelerating structure named Hybrid RFQ is proposed to accelerate a high-intensity low-energy heavy ion beam in HISCL （High Intensive heavy ion SuperConducting Linear accelerator）, which is an injector of HIAF （Heavy Ion Advanced Research Facility）. It is combined by an alternative series of acceleration gaps and RFQ sections. The proposed structure has a high accelerating ability compared with a conventional RFQ and is more compact than traditional DTLs. A Hybrid RFQ is designed to accelerate 238U34＋ from 0.38 MeV/u to 1.33 MeV/u. The operation frequency is described to be 81.25 MHz at CW （continuous wave） mode. The design beam current is 1.0 mA. The results of beam dynamics and RF simulation of the Hybrid RFQ show that the structure has a good performance at the energy range for ion acceleration. The emittance growth is less than 5% in both directions and the RF power is less than 150 kW. In this paper, the results of beam dynamics and RF simulation of the Hybrid RFQ are presented.